Feasible Relation between Glutathione Peroxidase and Febrile Seizure - MAHYAR, Abolfazl; AYAZI, Parviz; DALIRANI, Reza; MOHAMMAD HOSEINI, Behzad; SAROOKHANI, Mohammad Reza; JAVADI, Amir; ESMAEILY, Shiva (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Mahyar A, Ayazi P, Dalirani R, Mohammad Hoseini B, Sarookhani MR, Javadi A, Esmaeily Sh. Feasible Relation between Glutathione Peroxidase and Febrile Seizure. Iran J Child Neurol. Winter 2017; 11(1):65-69. Abstract Objective We aimed to determine the relationship between serum glutathione peroxidase and febrile seizure. Materials & Methods In this case-control study, 43 children with simple febrile seizure (case group) were compared with 43 febrile children without seizure (control group) in terms of serum glutathione peroxidase level, measured by ELISA method. This study was conducted in Qazvin Children Hospital, Qazvin University of Medical Sciences in Qazvin, Iran in 2012-2013. The results were analyzed and compared in two groups. Results From 43 children 24 (53%) were male and 19 (47%) were female in children with simple febrile seizure, and 26 (60%) were male and 17 (40%) were female in febrile children without seizure (control group) (P=0.827). Serum glutathione peroxidase level was 166 U/ml (SD=107) in the case group and 141 U/ml (SD=90.5) in the control group of no significant difference. Conclusion There was no significant relationship between serum glutathione peroxidase and simple febrile seizure. Thus, it seems that glutathione peroxidase, an essential component of antioxidant system, does not play any role in the pathogenesis of simple febrile seizure. References 1. Duffner PK, Baumann RJ, Berman P, Green JL, Schneider S, Hodgson ES, etal. Febrile seizures: clinical practice guideline for the long-term management of the child with simple febrile seizures. Pediatrics 2008 ;121:1281-6.Midline doi: 10.1542/peds.2008-0939. 2.Shinnar S. Febrile seizures. In: Swaiman KF, Ashwal S,Ferriero DM. Pediatric neurology: principles and practice. 4th ed. Philadelphia: Mosby, 2006:1079-86. 3. Mikati M A. Febrile seizures.In: Kliegman RM, Stanton B F, GemeIII J WS, Schor NF , Behrman RE. Nelson textbook of pediatrics.19th ed. Philadelphia: Saunders, 2011:2017-19. 4. Hara K, Tanabe T, Aomatsu T, Inoue N, Tamaki H, Okamoto N ,etal. Febrile seizures associated with influenza A. Brain and Development 2007;29: 30-38. 5. Sugai K.Current management of febrile seizures in Japan: An overview . Brain and Development 2010; 32: 64-7. Midline doi: 10.1016/j.braindev.2009.09.019. 6. Camfield P, Camfield C, Kurlemann G. Febrile seizures, epileptic syndromes in infancy, childhood, and adolescence. 3th ed. London: John Libbey & Co Ltd,2002:145–52. 7. Sapir D, Leitner Y, Harel S, Kraumer U. Unprovoked seizures after complex febrile convulsions. Brain Dev 2000; 22:484–6. 8. Kumari PL, Nair MK, Nair SM, Kailas L, Geetha S. Iron deficiency as a risk factor for simple febrile seizures--a case control study. Indian Pediatr 2012; 49:17-9. 9. Tutuncuoglu S, Kutukculer N, Kepe L, Coker C, Berdeli A, Tekgul H. Proinflammatory cytokines, prostaglandins and zinc in febrile convulsions. Pediatr Int 2001;43:235-9. 10. Ashrafi MR, Shams S, Nouri M, Mohseni M, Shabanian R, Yekaninejad MS, etal. A probable causative factor for an old problem: selenium and glutathione peroxidase appear to play important roles in epilepsy pathogenesis. Epilepsia 2007 ;48:1750-5. 11. Willmore IJ, Rubin JJ. Antiperoxidant pretreatment and iron-induced epileptiform discharges in the rat: EEG and histopathologic studies. Neurology1981; 31:63–69. 12.Irshad M, Chaudhuri PS. Oxidant-antioxidant system: role and significance in human body. Indian J Exp Biol 2002 ;40:1233-9. 13.Rayman MP.The importance of selenium to human health. Lancet 2000;356:233-41. 14.Patel M. Mitochondrial dysfunction and oxidative stress: cause and consequence of epileptic seizures. Free Radical Biology & Medicine 2004;37:1951–1962. 15.Li-Ping L, Patel M. Seizure induced changes in mitochondrial redox status. Free Radical Biology & Medicine 2006;40:316–322. 16. Weber GF, Maertens P, Meng XZ, Pippenger CE. Glutathione peroxidase deficiency and childhood seizures. Lancet 1991 15; 337:1443-4. 17. Sudha K, Rao AV, Rao A. Oxidative stress and antioxidants in epilepsy. Clin Chim Acta 2001; 303:19-24. 18. Verrotti A, Basciani F, Trotta D, Pomilio MP, Morgese G, Chiarelli F.Serum Copper, Zinc, Selenium, Glutathione peroxidase and Superoxide dismutase levels in epileptic children before and after 1 year of sodium valproate and carbamazepine therapy. Epilepsy Res 2002;48:71-5. 19. Ben-Menachem E. Kyllerman M, Marklund S. Superoxide dismutase and glutathione peroxidase function in progressive myoclonus epilepsies. Epilepsy Res 2000;40:33-9. 20. Turkdogan D, Toplan S, Karakoc Y. Lipid peroxidation and antioxidative enzyme activities in childhood epilepsy. J Child Neurol 2002; 17:673-6. 21.Naziroglu M, Kutluhan S, Yilmaz M. Selenium and topiramate modulates brain microsomal oxidative stress values, Ca2+-ATPase activity, and EEG records in pentylenetetrazol-induced seizures in rats. J Membr Biol 2008;225:39-49. 22.Naziroglu M. Role of selenium on calcium signaling and oxidative stress-induced molecular pathways in epilepsy. Neurochem Res 2009; 34:2181-91.Medline doi: 10.1007/s11064-009-0015-8. 23.Brigelius-Flohé R, Maiorino M.Glutathione peroxidases. Biochim Biophys Acta 2013 ;1830:3289-303. 24. Harapin I, Bauer M, Bedrica L, Potoanjak D. Correlation between gluthathione peroxidase activity and the quantity of selenium in the whole blood of beef calves. Acta Vet Brno 2000; 69: 87–92.Medline. doi: 10.1016/j.bbagen.2012.11.020. 25.Koller LD, South PJ, Exon JH, Whitbeck GA, Maas J. Comparison of selenium levels and glutathione peroxidase activity in bovine whole blood. Can J Comp Med 1984 ;48:431-3.